2018
DOI: 10.1088/1361-6528/aaa62d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelet doping of P3HT:PCBM photoactive layer of bulk heterojunction organic solar cells for enhancing performance

Abstract: Hybrid organic photovoltaic (OPV) cells based on conjugated polymers photoactive materials are promising candidates for flexible, high-performance and low-cost energy sources owing to their inexpensive materials, cost-effective processing, and ease of fabrication by simple solution processes. However, the modest PV performance obtained to date -in particular the low power conversion efficiency (PCE)- has impeded the large scale deployment of OPV cells. The low PCE in OPV solar cells has been mainly attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…The control device produced with a nondoped PEDOT:PSS layer showed a PCE of 2.25% with a J sc of 12.15 mA cm −2 , a V oc of 0.455 V, and a FF of 40.7%. This PCE is comparable to results reported in the literature, which can be seen in Table 2 [31][32][33][34][35]. In comparison to the control device, all devices fabricated with a doped PEDOT:PSS layer yielded superior PCE thanks to enhanced V oc and J sc values, while the FF values were mostly unchanged.…”
Section: Resultssupporting
confidence: 87%
“…The control device produced with a nondoped PEDOT:PSS layer showed a PCE of 2.25% with a J sc of 12.15 mA cm −2 , a V oc of 0.455 V, and a FF of 40.7%. This PCE is comparable to results reported in the literature, which can be seen in Table 2 [31][32][33][34][35]. In comparison to the control device, all devices fabricated with a doped PEDOT:PSS layer yielded superior PCE thanks to enhanced V oc and J sc values, while the FF values were mostly unchanged.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, the intensities of the (100) and (002) peaks drastically increased in the P3HT/EEG 10 nanocomposite film, which implies that the optimal content of EEG in the composite film can induce higher crystallinity and stronger intermolecular interactions. It has been reported that the P3HT molecules has more ability to crystallize in the composite film because the thiophene rings in a P3HT chain becomes interconnected with sp 2 -hybridized graphene surface [40,41].…”
Section: Preparation and Characterization Of Ofet Based On The P3ht/ementioning
confidence: 99%
“…[24][25][26][27][28][29] In the latter case, a wide range of additives have been investigated whose complimentary optical or electronic properties enable them to enhance the range of light absorbed, [30][31][32] facilitate more efficient electron or hole transport 33 or modify the morphology of the devices leading to improvements in performance and stability. [34][35][36] Two-dimensional materials are ideal candidates for use as additives thanks to their large surface areas and distinct electronic and optical properties. [37][38][39] Transition metal dichalcogenides (TMDCs) in particular have attracted signicant interest because of their thicknessdependant opto-electronic properties, 40 ambipolar charge transport, 41 chemical stability and direct band-gaps in the single layer form.…”
Section: Introductionmentioning
confidence: 99%